An observational MRI study on lower back pain correlating age-associated lumbar spine changes and degenerative pathologies - Pandey, Piyush; Panda, Mamta; Khan, M. Usman; Kumar Diwakar, Shailendra (International Journal Of Community Medicine And Public Health, 2025)
Background: One of the most prevalent medical complaints is lower back pain, which may vary in severity from moderate to severe. It might develop chronic and persist for many months or even longer, or it can be acute and only last for a few days to a few weeks. Variations in the size of the lumber spinal canal are caused by a variety of factors, including trauma or injury, obesity, arthritis, herniated or bulging discs, sciatica, and muscle or ligament tension. Methods: A convenient sample of thirty patients, aged 20 to 70, both male and female, were included in this prospective observational study. At the time of the initial examination, a complete history of the individual was obtained, including any reports from prior MRI investigations or any other prior history relevant to the current study. Results: The research included 30 patients, half of them were male and half of them were female. The majority of patients were between the age of 20 and 40. Degenerative alterations such as disc herniation, nerve root compression, and disc desiccation were the most common causes of lower back pain, leading to changes in spinal canal dimensions, and were shown to be most common in individuals aged 40 to 60 years. Conclusions: This research aimed to estimate the occurrence of inter-vertebral disc problems in different age groups, analysing the relationship between degenerative changes in the lumbar spine and changes in the spinal cord due to age.